Vertical Migration Optimizes Photosynthetic Efficiency of Motile Cyanobacteria in a Coastal Microbial Mat - Lichtenberg, Mads; Cartaxana, Paulo; Kühl, Michael (Frontiers in Marine Science, 2020)
Microbial mats are diverse and stratified microbial biofilm communities characterized by steep gradients in light, temperature and chemical parameters. Their high optical density creates a competition for light among phototrophic microalgae and bacteria residing in the uppermost mat layers. Strategies to counter such resource limitation include metabolic investment in protective and light-harvesting pigments enabling exploitation of separate niches in terms of irradiance and spectral composition, or investment in motility to enable migration to an optimal light microenvironment. We used microsensor measurements of light, temperature and gross photosynthesis in coastal microbial mats dominated by motile cyanobacteria and colorless sulfur bacteria to study how migration affected their radiative energy-budgets and relative photosynthetic efficiency. The optical density of the microbial mat was extremely high, and >99% of incident irradiance of visible light (400-700 nm) was attenuated <0.4 mm below the surface. While energy conservation efficiency did not change dramatically with previous light acclimation, vertical profiles of photosynthetic efficiency showed a shift in the position of maximum efficiency of 0.2 mm, depending on light treatment. Besides avoidance of unfavorable chemical conditions such as high sulfide levels, vertical migration over short distances thus enable cyanobacteria to track zones with optimal light exposure thereby efficiently counteracting detrimental effects of excessive light at the surface and insufficient light deeper in the mat.